Electromagnetic homeostasis and the role of low-amplitude electromagnetic fields on life organization. (3rd April 2017) - De Ninno, Antonella; Pregnolato, Massimo
ABSTRACT: The appearance of endogenous electromagnetic fields in biological systems is a widely debated issue in modern science. The electrophysiological fields have very tiny intensities and it can be inferred that they are rapidly decreasing with the distance from the generating structure, vanishing at very short distances. This makes very hard their detection using standard experimental methods. However, the existence of fast-moving charged particles in the macromolecules inside both intracellular and extracellular fluids may envisage the generation of localized electric currents as well as the presence of closed loops, which implies the existence of magnetic fields. Moreover, the whole set of oscillatory frequencies of various substances, enzymes, cell membranes, nucleic acids, bioelectrical phenomena generated by the electrical rhythm of coherent groups of cells, cell-to-cell communication among population of host bacteria, forms the increasingly complex hierarchies of electromagnetic signals of different frequencies which cover the living being and represent a fundamental information network controlling the cell metabolism. From this approach emerges the concept of electromagnetic homeostasis: that is, the capability of the human body to maintain the balance of highly complex electromagnetic interactions within, in spite of the external electromagnetic noisy environment. This concept may have an important impact on the actual definitions of heal and disease.